Magnesium Sulfate and Fentanyl for Facilitating Awake Fiberoptic Nasotracheal Intubation: A Randomized Study - Dhiman, Shweta; Bhalotra, Anju Romina; Kumari, Ruchi; Sharma, Kavita Rani; Verma, Uttam Chand (Annals of Anesthesiology and Critical Care, 2019)
Background: Various drugs have been used to facilitate awake fiberoptic intubation (AFOI). Although fentanyl is probably used most frequently, magnesium sulfate can provide muscle relaxation without respiratory depression and attenuate hemodynamic responses. Methods: We randomly allocated 20 patients of both sexes, aged 18 - 60 years, and ASA status I-II to receive fentanyl 2 _g/kg (group F) or magnesium sulfate 45 mg/kg (group M) before AFOI. The intubating conditions were evaluated by Ramsay sedation score (RSS), cough score, post-intubation score, additional topicalization requirement, and hemodynamic response. Oxygen desaturation, airway morbidity, recall of procedure, and the patient’s willingness to return for the same kind of anesthesia, if required, were also studied. Statistical analyses were done using SPSS V. 17.0 software. Numerical data were analyzed using independent and paired t-tests and categorical data using the chi-square test. P values of < 0.05 were considered significant. Results: RSS, cough score, post-intubation score, lignocaine dose, airway-related morbidity, and willingness to undergo the same kind of anesthesia for a second time were comparable between thetwogroups. Both drugshadcomparable effectsonhemodynamic response to intubation. However, the incidence of recall of the procedure was significantly lower in group F (P = 0.003). Conclusions: The degree of coughing during fiberoptic bronchoscopy, tolerance of the endotracheal tube after intubation, and the hemodynamic response to intubation were similar after the administration of either fentanyl 2 _g/kg or magnesium sulfate 45 mg/kg.